Объяснение:
ZnCl2 + 2NaOH = Zn(OH)2↓ + 2NaCl
Zn(2+) + 2Cl(-) + 2Na(+) + 2OH(-) = Zn(OH)2↓ + 2Na(+) + 2Cl(-)
Zn(2+) + 2OH(-) = Zn(OH)2↓
Ba(NO3)2 + K2SO4 = BaSO4↓ + 2KNO3
Ba(2+) + 2NO3(-) + 2K(+) + SO4(2-) = BaSO4↓ + 2K(+) + 2NO3(-)
Ba(2+) + SO4(2-) = BaSO4↓
AlCl3 + 3KOH = Al(OH)3↓ + 3KCl
Al(3+) + 3Cl(-) + 3K(+) + 3OH(-) = Al(OH)3↓ + 3K(+) + 3Cl(-)
Al(3+) + 3OH(-) = Al(OH)3↓
FeCl2 + 2KOH = Fe(OH)2↓ + 2KCl
Fe(2+) + 2Cl(-) + 2K(+) + 2OH(-) = Fe(OH)2↓ + 2K(+) + 2Cl(-)
Fe(2+) + 2OH(-) = Fe(OH)2↓
Pb(NO3)2 + Na2SO4 = PbSO4↓ + 2NaNO3
Pb(2+) + 2NO3(-) + 2Na(+) + SO4(2-) = PbSO4↓ + 2Na(+) + 2NO3(-)
Pb(2+) + SO4(2-) = PbSO4↓
ZnCl2 + 2NaOH = Zn(OH)2↓ + 2NaCl
Zn(2+) + 2Cl(-) + 2Na(+) + 2OH(-) = Zn(OH)2↓ + 2Na(+) + 2Cl(-)
Zn(2+) + 2OH(-) = Zn(OH)2↓
Объяснение:
ZnCl2 + 2NaOH = Zn(OH)2↓ + 2NaCl
Zn(2+) + 2Cl(-) + 2Na(+) + 2OH(-) = Zn(OH)2↓ + 2Na(+) + 2Cl(-)
Zn(2+) + 2OH(-) = Zn(OH)2↓
Ba(NO3)2 + K2SO4 = BaSO4↓ + 2KNO3
Ba(2+) + 2NO3(-) + 2K(+) + SO4(2-) = BaSO4↓ + 2K(+) + 2NO3(-)
Ba(2+) + SO4(2-) = BaSO4↓
AlCl3 + 3KOH = Al(OH)3↓ + 3KCl
Al(3+) + 3Cl(-) + 3K(+) + 3OH(-) = Al(OH)3↓ + 3K(+) + 3Cl(-)
Al(3+) + 3OH(-) = Al(OH)3↓
FeCl2 + 2KOH = Fe(OH)2↓ + 2KCl
Fe(2+) + 2Cl(-) + 2K(+) + 2OH(-) = Fe(OH)2↓ + 2K(+) + 2Cl(-)
Fe(2+) + 2OH(-) = Fe(OH)2↓
Pb(NO3)2 + Na2SO4 = PbSO4↓ + 2NaNO3
Pb(2+) + 2NO3(-) + 2Na(+) + SO4(2-) = PbSO4↓ + 2Na(+) + 2NO3(-)
Pb(2+) + SO4(2-) = PbSO4↓
ZnCl2 + 2NaOH = Zn(OH)2↓ + 2NaCl
Zn(2+) + 2Cl(-) + 2Na(+) + 2OH(-) = Zn(OH)2↓ + 2Na(+) + 2Cl(-)
Zn(2+) + 2OH(-) = Zn(OH)2↓
2KNO3 + H2SO4 ( конц) = 2HNO3 + K2SO4.
HNO3 + NH3 = NH4NO3
3NH4NO3 + BaCO3 = 4NH3 + CO2 + Ba(NO3)2
3Ba(NO3)2 + Al2(SO4)3 = 3BaSO4( осадок ) + 2Al(NO3)3